UNSTEADY FLOW OF CASSON NANOFLUID THROUGH GENERALIZED FOURIER'S AND FICK'S LAW FOR HEAT AND MASS TRANSFER - Wang, Ye-Qi; Shafique, Ahmad; Nisa, Zaib; Asjad, Muhammad; Nazar, Mudassar; İnç, Mustafa; Yao, Shao-Wen (Vinca Inst Nuclear Sci, 2022)
The purpose of this paper to explain the role and importance of fractional derivatives for mass and heat transfer in Casson nanofluids including clay nanoparticles. These particles can be found in water, kerosene, and engine oil. The physical flow phenomena are illustrated using PDE and thermophysical nanoparticle properties, and this paper addresses the Casson fractional fluid along with chemical reaction and heat generation. The heat and mass fluxes are generalized using the constant proportional Caputo fractional derivative. The present flow model are solved semi-analytically using the Laplace transform. We generated several graphs to understand how various flow factors affect velocity. The acquired results reveal that fractional parameters have dual behavior in velocity profiles. Velocity and temperature are also compared to previous studies. Compared to the other fractional derivatives results, field variables and proposed hybrid fractional derivatives showed a more decaying trend. Furthermore, significant results of clay nanoparticles with various base fluids have been obtained.
Keywords: Casson fluid; clay nanoparticles; heat generation; chemical reaction; constant proportional Caputo; fractional derivative